Development of Mobile Game Application: Escape Room No Pest! - Talib, Siti NurFaridah; Suparjoh, Suriawati (Applied Information Technology And Computer Science, 2026)
Pest control is a critical component of agricultural education, equipping students with essential knowledge to manage and prevent pest-related issues in farming. However, educational tools designed specifically for Form 5 students studying agriculture are still limited. This project proposes the development of a 3D mobile game tailored to the agricultural curriculum, focusing on key topics such as pest control management, relevant legislation, and standard procedures. The game incorporates challenges related to agricultural activities, enabling students to apply their knowledge in managing pests, understanding legal frameworks, and implementing appropriate procedures. The Game Development Life Cycle (GDLC) methodology is utilized to ensure a structured and efficient development process, creating an educational experience that aligns with students’ learning needs. Testing and evaluation was conducted using System Usability Scale (SUS) measurement with the percent of 68.63%. This application aims to enhance students’ understanding of pest control while fostering critical thinking and practical problem-solving skills in agriculture.